Infliximab in treatment of idiopathic refractory childhood pyoderma gangrenosum (PG) - Salehzadeh F (Dove Medical Press, 2019)
Farhad Salehzadeh,1 Yusef Mohammadikebar,2 Afsaneh Enteshary,2 Omid Ghanbarpour,1 Mehrdad Mirzarahimi11Department of Pediatric, Bouali Children’s Hospital, Ardabil University of Medical Sciences (ARUMS), Ardabil, Iran; 2Department of Internal Medicine, Emam Khomeini Hospital, Ardabil University of Medical Sciences (ARUMS), Ardabil, IranAbstract: We report a case of refractory idiopathic childhood pyoderma gangrenosum in a young boy who had suffered from this disease since 3 years of age. He had unfavorable responses and intermittent relapses under different combinations of cytotoxic and steroid therapies. Although there was not much information available about infliximab use for biologic and childhood pyoderma gangrenosum, eventually we decided to use infliximab in this patient. Infliximab showed a dramatic response and resulted in full recovery during 2 years’ follow-up.Keywords: pyoderma gangrenosum, infliximab, childhood